Sistem Informasi Akuntansi Multiuser dalam Operasional Usaha Rental Mobil CV. Ranggawarsita Tour - Endaryati, Eni; Sri Wahyuning; Sukemi Kamto Sudibyo; Fransiska Bhoko (Jurnal Manajemen Informatika & Teknologi, 2025)
The advancement of information technology has encouraged various business sectors, including transportation services, to carry out digital transformation. This study aims to create a multi-user-based accounting information system and implement it in CV. Ranggawarsita Tour, a car rental company in Semarang that previously used manual methods. The system development uses SDLC and data is obtained directly through interviews and surveys in the company as well as literature studies. The system developed has proven to be able to increase efficiency in documenting transactions, processing customer data, and compiling financial information quickly and on time. The system was created using the PHP and MySQL programming languages ​​to store data. The results of this study conclude that a multi-user-based accounting information system overcomes operational obstacles and provides support to companies in providing reliable financial information.